Raman Spectroscopy to Characterize Bladder Tissue for Multidimensional Diagnostics of Cancer in Urology - Krafft C. (De Gruyter, 2020)
Fiber optic Raman spectroscopy offers labelfree identification of cancer in the bladder under in vivo conditions. However, state-of-the-art Raman technology does not enable to scan the entire bladder wall. Our multidimensional approach within the project Uro-MDD combines panoramic 3D-image reconstruction of white light cystoscopy and fluorescence lifetime imaging to define regions of interest for Raman-assisted diagnostics. First Raman results are presented from human control and cancer bladder specimens that demonstrated how to obtain specific molecular information. Such Raman images can be used in a clinical setting to determine cancer margins and the resection status. Fiber probes are under development to translate the technique to in vivo screening.